100% SVR with Ledipasvir/Sofosbuvir Plus Ribavirin in Patients with HCV GT-1 Failing Prior Therapy - Rizzo, Toni (MD Conference Express, 2014)
This article discusses a study was to evaluating the efficacy of ledipasvir/sofosbuvir fixed-dose combination in treatment-experienced patients with hepatitis C virus genotype 1 who failed to achieve SVR at week 12 with prior sofosbuvir-based therapy.